Effect of welding parameters on bead characteristics and mechanical properties of wire and arc additive manufactured inconel 718. (April 2023) - Kumar, Parveen; Singh, Ratnesh Kumar Raj; Sharma, Satish Kumar
In this study, a bi-directional, low-cost, gas metal arc welding (GMAW) based wire arc additive manufacturing (WAAM) setup is used to deposit aerospace-grade super-alloy IN718. The orthogonally designed experiments are carried out to optimize process parameters for bead geometry characteristics. Study result shows that with an increase in heat input, the bead parameters like bead width, reinforcement, dilution, penetration, and weld form factor are increasing, while it has a detrimental effect on weld shape factor and wetting angle. Microstructural examination reveals that at high heat input, coarser grain structure having average grain size of 72.29 µm is obtained while at low heat input, a finer grain structure with average grain size of 32.12 µm along with smaller amount of Laves phases are present. The XRD reveals NbC and TiC phases present in case of low heat input sample which enhances the mechanical properties of deposited material. The multilayer wall structures fabricated at high heat input showed more uniformity in shape with lesser waviness than that fabricated with low heat input. The tensile result of low heat input sample (775.82 MPa) shows higher strength than high heat input sample (741.07 MPa) which is because of smaller grain structure and higher hardness (278.11 HV) as obtained in low heat input sample as compared to high heat input sample (257.26 HV). The EBSD analysis also confirms highly textured surface, more grain boundary lengths and larger grain boundary orientation in low heat input sample imparted better mechanical properties.